2022
DOI: 10.3389/fphys.2022.841056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydration with beverages containing free sugars or xylitol on metabolic and acute kidney injury markers after physical exercise

Abstract: The proper fluid and carbohydrates intake is essential before and during physical exercise, and for this reason most athletes drink beverages containing a high amount of free sugars. Sweetened soft drinks are also commonly consumed by those not doing any sport, and this habit seems to be both unhealthy and also the cause of metabolic problems. Recently, several sweeteners have been proposed to replace sugars in popular beverages. To examine the impact of free sugars and the popular sweetener xylitol on metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Gastrointestinal tolerance in our trial was good except for a few diarrhoea-related symptoms at the beginning of the intervention, especially in the xylitol group. This is in line with other studies, showing that the acute consumption of xylitol might cause some gastrointestinal inconvenience,19 39 and that subjects over time adapt to chronic intake 40…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gastrointestinal tolerance in our trial was good except for a few diarrhoea-related symptoms at the beginning of the intervention, especially in the xylitol group. This is in line with other studies, showing that the acute consumption of xylitol might cause some gastrointestinal inconvenience,19 39 and that subjects over time adapt to chronic intake 40…”
Section: Discussionsupporting
confidence: 92%
“…We have previously found that acute ingestion of 35 g xylitol led to an increase in uric acid, while there was no effect after 50 g erythritol 18 19. An increase in uric acid was also found in an acute study in healthy volunteers given 35 g xylitol during physical exercise 39. Förster et al 27 reported that plasma uric acid was unchanged in healthy volunteers after 18 days of up to 100 g/day xylitol consumption.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Wolyniec et al [ 86 ] found an increase in uric acid after oral administration of sucrose, glucose, fructose, or xylitol (for all, 35 g in 500 mL water) in healthy participants. This increase was the highest after xylitol, and was similar after the three conventional sweeteners.…”
Section: Effects On Uric Acidmentioning
confidence: 99%
“…It has been shown that acute ingestion of 35 g of xylitol in 300 mL or 500 mL water leads to an increase in uric acid concentrations in healthy volunteers [ 33 , 86 ]. However, a chronic administration of xylitol (24 g/day) for five weeks had no effect on uric acid concentrations in participants with obesity, but who were otherwise healthy [ 75 ].…”
Section: Effects On Uric Acidmentioning
confidence: 99%